2011
DOI: 10.1007/s10658-011-9774-6
|View full text |Cite
|
Sign up to set email alerts
|

Selection of species resistant to the wood rot fungus Phellinus noxius

Abstract: Brown root rot, caused by the pathogen Phellinus noxius, has been reported throughout Southeast Asia, Oceania and Africa as a cause of tree decline and mortality. This paper describes how a field survey can be used to quickly select species that are locally resistant to Phellinus noxius by performing qualitative and quantitative analyses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…In West Africa and China, brown root rot was reported as the most devastating root disease attacking the rubber plantations (Nandris et al., ). Trees in urban areas and plantation forests in Hong Kong and Macao have also been seriously affected (Huang, Sun, Bi, Zhong, & Hu, ; Wu et al., ). Field observations support the root‐to‐root spread as a major transmission mode of the epidemic.…”
Section: Introductionmentioning
confidence: 99%
“…In West Africa and China, brown root rot was reported as the most devastating root disease attacking the rubber plantations (Nandris et al., ). Trees in urban areas and plantation forests in Hong Kong and Macao have also been seriously affected (Huang, Sun, Bi, Zhong, & Hu, ; Wu et al., ). Field observations support the root‐to‐root spread as a major transmission mode of the epidemic.…”
Section: Introductionmentioning
confidence: 99%
“…An ammonia‐based chemical reagent has been developed that is effective against brown root rot disease development, but results have shown that this particular reagent has adverse effects on soil characteristics and root growth 7, 8. Alternative approaches are to flood or replant infected areas.…”
Section: Introductionmentioning
confidence: 99%
“…Alternative approaches are to flood or replant infected areas. Wu et al 7 have published an effective selection method entailing the replanting of infected areas with plant species that are resistant to P. noxius ; however, these approaches may have some limitations with respect to geographical conditions and land utilisation for agriculture.…”
Section: Introductionmentioning
confidence: 99%
“…D espite favoring w oody t rees, P. noxius can also attack some herbaceous pl ants [2,5,6] . P. noxius has be en f ound i n many t ropical a nd s ubtropical c ountries and di stricts, including Singapore, Japan, Indonesia, Malaysia, Hai-T nan Island in China, Macao, Taiwan, Africa, Australia, Central America, and the Caribbean [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] . The wide geographical distribution of this pathogen and the severe da mage i t ha s caus ed have d rawn significant concerns.…”
Section: Introductionmentioning
confidence: 99%